Occurrence of Glomerella cingulata (Colletotrichum gloeosporioides) in dormant floral buds and flowers of apple - Bernardi, João; Feliciano, Alberto; de Assis, Márcio (Pesquisa Agropecuaria Brasileira, 2014)
Glomerella cingulata (Ston.) Spauld et Schrenk (Colletotrichum gloeosporiaides Penz), the causal agent of bitter rot of apple, was isolated starting in July in the inner and outer parts of the dormant flower buds. In the open flowers, the fungus was isolated in all different flower parts in three stages of flower development studied.
Keywords: bitter rot; Malus domestica